We will learn the transformation of general form into normal form.
To reduce the general equation Ax + By + C = 0 into normal form (x cos α + y sin α = p):
We have the general equation Ax + By + C = 0.
Let the normal form of the given equation ax + by + c = 0……………. (i) be
x cos α + y sin α - p = 0, where p > 0. ……………. (ii)
Then, the equations (i) and (ii) are the same straight line i.e., identical.
⇒ \(\frac{A}{cos α}\) = \(\frac{B}{sin α}\) = \(\frac{C}{-p}\)
⇒ \(\frac{C}{P}\) = \(\frac{-A}{cos α}\) = \(\frac{-B}{sin α}\) = \(\frac{+\sqrt{a^{2} + b^{2}}}{\sqrt{cos^{2} α + sin^{2} α}}\) = + \(\sqrt{A^{2} + B^{2}}\)
Therefore, p = \(\frac{C}{\sqrt{A^{2} + B^{2}}}\), cos α = - \(\frac{A}{\sqrt{A^{2} + B^{2}}}\) and sin α = - \(\frac{B}{\sqrt{A^{2} + B^{2}}}\)
So, putting
the values of cos α, sin α and p in the equation (ii) we get the form,
⇒ - \(\frac{A}{\sqrt{A^{2} + B^{2}}}\) x - \(\frac{B}{\sqrt{A^{2} + B^{2}}}\) y - \(\frac{C}{\sqrt{A^{2} + B^{2}}}\) = 0, when c > 0
⇒ \(\frac{A}{\sqrt{A^{2} + B^{2}}}\) x + \(\frac{B}{\sqrt{A^{2} + B^{2}}}\) y = - \(\frac{C}{\sqrt{A^{2} + B^{2}}}\), when c < 0
Which is the required normal form of the general form of equation Ax + By + C = 0.
Algorithm to Transform the General Equation to Normal Form
Step I: Transfer the constant term to the right hand side and make it positive.
Step II: Divide both sides by \(\sqrt{(\textrm{Coefficient of x})^{2} + (\textrm{Coefficient of y})^{2}}\).
The obtained equation will be in the normal form.
Solved examples on transformation of general equation into normal form:
1. Reduce the line 4x + 3y - 19 = 0 to the normal form.
Solution:
The given equation is 4x + 3y - 19 = 0
First shift the constant term (-19) on the RHS and make it positive.
4x + 3y = 19 ………….. (i)
Now determine \(\sqrt{(\textrm{Coefficient of x})^{2} + (\textrm{Coefficient of y})^{2}}\)
= \(\sqrt{(4)^{2} + (3)^{2}}\)
= \(\sqrt{16 + 9}\)
= √25
= 5
Now dividing both sides of the equation (i) by 5, we get
\(\frac{4}{5}\)x + \(\frac{3}{5}\)y = \(\frac{19}{5}\)
Which is the normal form of the given equation 4x + 3y - 19 = 0.
2. Transform the equation 3x + 4y = 5√2 to normal form and find the perpendicular distance from the origin of the straight line; also find the angle that the perpendicular makes with the positive direction of the x-axis.
Solution:
The given equation is 3x + 4y = 5√2 ……..….. (i)
Dividing both sides of equation (1) by + \(\sqrt{(3)^{2} + (4)^{2}}\) = + 5 we get,
⇒ \(\frac{3}{5}\)x + \(\frac{4}{5}\)y = \(\frac{5√2}{5}\)
⇒ \(\frac{3}{5}\)x + \(\frac{4}{5}\)y = √2
Which is the normal form of the given equation 3x + 4y = 5√2.
Therefore, the required, perpendicular distance from the origin of the straight line (i) is √2 units.
If the perpendicular makes an angle α with the positive direction of the x-axis then,
cos α = \(\frac{3}{4}\) and sin α = \(\frac{4}{5}\)
Therefore, tan α = \(\frac{sin α}{cos α }\) = \(\frac{\frac{4}{5}}{\frac{3}{5}}\) = \(\frac{4}{3}\)
⇒ α = tan\(^{-1}\)\(\frac{4}{3}\).
● The Straight Line
11 and 12 Grade Math
From General Form into Normal Form to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Sep 17, 24 02:25 AM
Sep 17, 24 01:47 AM
Sep 17, 24 12:10 AM
Sep 16, 24 11:24 PM
Sep 16, 24 02:40 PM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.